Antimicrobial drug resistance and infection prevention/control: lessons from tuberculosis - Cegielski, J. Peter; Tudor, Carrie; Volchenkov, Grigory V.; Jensen, Paul A. (International Journal of Infection Control, 2021)
Antimicrobial drug resistance (AMR) is increasing rapidly worldwide, causing an estimated 700,000 deaths annually over the past decade, en route to becoming the leading global threat to public health by 2050 with an estimated 10 million deaths per year (more than heart disease, cancer, and stroke), while reducing global wealth by US100 trillion. Yet AMR has not received the attention and action required to change this trajectory. Appropriate infection prevention and control (IPC) measures are needed to prevent transmission of infections to healthcare workers (HCWs), other patients, families, and the general public. In this review, we discuss a notable case study of AMR: highly drug-resistant tuberculosis (TB) has emerged repeatedly over the past 70 years as new drugs have been introduced, leading to new diagnostics, therapeutics, funding, public health strategies, and, in high-income countries, effective IPC measures that curtailed transmission. We review current efforts to control and prevent AMR using the example of drug-resistant tuberculosis to highlight important themes including laboratory systems, surveillance, control and prevention of healthcare-associated infections (especially among HCWs), better coordination across disciplines and diseases, and powerful advocacy/social change initiatives grounded in social and behavioral sciences. These strategies are the foundation of an effective response to the AMR threat to public health.